2008
DOI: 10.3171/jns/2008/109/11/0825
|View full text |Cite
|
Sign up to set email alerts
|

Resection of insular gliomas: the importance of lenticulostriate artery position

Abstract: Insular gliomas with an MR imaging-defined tumor volume located lateral to the LSAs on stereotactic angiography displace the LSAs medially by expanding the insula, have well-demarcated tumor boundaries on MR images, and can be completely resected with minimal neurological morbidity. In contrast, insular tumors that appear to surround the LSAs do not displace these vessels medially, are poorly demarcated from normal brain parenchyma on MR images, and are associated with higher rates of neurological morbidity if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
0
35

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(127 citation statements)
references
References 23 publications
2
90
0
35
Order By: Relevance
“…Thus, they represent a very important deep limit to prevent any damage to perforating arteries, explaining why no stroke occurred in the present selected subset of patients who underwent operations while awake, contrary to the other patient series reported in the literature in which permanent deficits were always observed, mostly due to vascular injury. 33,38,39,47,50,53,54 On the other hand, because most paralimbic Grade II gliomas migrate along the fasciculi 35 and then into the anterior perforating substance, 12 preservation of functional pathways under the insula also explains why only 3 patients underwent a complete resection in this series (Table 2), in addition to the 5 patients with a left insula still involved in language, as mentioned above.…”
Section: Intraoperative Mappingmentioning
confidence: 87%
See 2 more Smart Citations
“…Thus, they represent a very important deep limit to prevent any damage to perforating arteries, explaining why no stroke occurred in the present selected subset of patients who underwent operations while awake, contrary to the other patient series reported in the literature in which permanent deficits were always observed, mostly due to vascular injury. 33,38,39,47,50,53,54 On the other hand, because most paralimbic Grade II gliomas migrate along the fasciculi 35 and then into the anterior perforating substance, 12 preservation of functional pathways under the insula also explains why only 3 patients underwent a complete resection in this series (Table 2), in addition to the 5 patients with a left insula still involved in language, as mentioned above.…”
Section: Intraoperative Mappingmentioning
confidence: 87%
“…Nonetheless, several reports in the past decade have demonstrated that it was possible to perform insular glioma resection with substantial but acceptable complication rates. 12,17,23,25,29,33,38,39,47,50,53,54 Surprisingly, most of these studies were mainly focused on motor function, in particular with the use of intraoperative motor tract monitoring, 40 while possible language disturbances have not been accurately assessed using an extensive and longitudinal examination by a speech therapist. In this paper, we report for the first time the results of an objective language examination performed by a speech therapist before, during, immediately after, and 3 months after an awake surgery for a Grade II glioma involving the dominant insula in a homogeneous series of 24 patients.…”
Section: Sulamentioning
confidence: 99%
See 1 more Smart Citation
“…Surgery of the insular area is known to be challenging because of its close relationship with vascular structures. 8,15,26,36,[38][39][40] Immediate postoperative deficits have been previously reported with incidence rates between 9.2% and 74% in the literature. Comparison in incidence rate of transient or permanent complications is difficult considering that these series have mostly dealt with patients with tumors or vascular malformations often extending outside the insula both to surrounding lobes and in deeper subcortical structures.…”
Section: Discussionmentioning
confidence: 99%
“…5,6,39,40 Motor evoked potentials (MEPs) and somatosensory evoked potentials (SSEPs) were also recorded during surgery, to continuously monitor the integrity of motor and somatosensory pathways (64-channel Eclipse Neurovascular Workstation, Axon Systems, Inc.; 32-channel video polygraphic station, Brain Quick SystemPlus, MicroMed). The selection of the anesthesiological protocol was based on the preoperative evaluation of hemispheric dominance.…”
Section: Surgical Procedures and Intraoperative Electrocorticographymentioning
confidence: 99%